Expression and Localization of AβPP in SH-SY5Y Cells Depends on Differentiation State - Riegerová, Petra; Brejcha, Jindřich; Bezděková, Dagmar; Chum, Tomáš; Mašínová, Eva; Čermáková, Nikola; Ovsepian, Saak V; Cebecauer, Marek; Štefl, Martin (Journal of Alzheimer's disease, 2021)
Neuroblastoma cell line SH-SY5Y, due to its capacity to differentiate into neurons, easy handling, and low cost, is a common experimental model to study molecular events leading to Alzheimer's disease (AD). However, it is prevalently used in its undifferentiated state, which does not resemble neurons affected by the disease. Here, we show that the expression and localization of amyloid-β protein precursor (AβPP), one of the key molecules involved in AD pathogenesis, is dramatically altered in SH-SY5Y cells fully differentiated by combined treatment with retinoic acid and BDNF. We show that insufficient differentiation of SH-SY5Y cells results in AβPP mislocalization.
Keywords: SH-SY5Y; AβPP; biologické modely; amyloidový prekurzorový protein beta; proteolýza; Proteolysis; oxidační stres; Cell Line, Tumor; Tretinoin; tretinoin; super-resolution microscopy; Oxidative Stress; Intravital Microscopy; buněčná diferenciace; lidé; Models, Biological; neurony; Neurons; Alzheimer’s disease; differentiation; Alzheimer Disease; Brain-Derived Neurotrophic Factor; Neuroblastoma; Alzheimerova nemoc; Amyloid beta-Protein Precursor; mozkový neurotrofický faktor; intravitální mikroskopie; Cell Differentiation; neuroblastom; nádorové buněčné linie; Humans